2022
DOI: 10.3389/fpsyt.2022.902909
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Age-Related Changes Among Middle-Aged and Older Adults: Longitudinal Trajectories, and the Role of Age Stereotypes and Personality Traits

Abstract: Awareness of Age-Related Change (AARC) describes to what extent people become aware of changes which they attribute to getting older. So far little is known regarding how different AARC dimensions change over time, to what extent these changes in different domains of AARC gains and losses are interrelated, and which predictors account for inter-individual differences in within-person longitudinal trajectories. Specifically, the extent to which individuals perceive age-related gains and losses might be shaped b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 100 publications
(147 reference statements)
0
5
0
Order By: Relevance
“…In support of this reasoning, a study using latent profile analyses (19) showed that while some middle-aged and older individuals report concurrent high levels of AARC losses and low levels of AARC gains, others report both high levels of AARC losses and high levels of AARC gains. Moreover, other empirical studies (5,36) have shown that levels of AARC gains are only minimally correlated to levels of AARC losses, suggesting that perceived gains are fairly independent from perceived losses. Another interesting finding was that there were statistically significant correlations between the ".…”
Section: Discussionmentioning
confidence: 87%
“…In support of this reasoning, a study using latent profile analyses (19) showed that while some middle-aged and older individuals report concurrent high levels of AARC losses and low levels of AARC gains, others report both high levels of AARC losses and high levels of AARC gains. Moreover, other empirical studies (5,36) have shown that levels of AARC gains are only minimally correlated to levels of AARC losses, suggesting that perceived gains are fairly independent from perceived losses. Another interesting finding was that there were statistically significant correlations between the ".…”
Section: Discussionmentioning
confidence: 87%
“…With regard to evidence on AARC, Kaspar et al (2022) found that AARC-gains decreased and AARC-losses increased as people moved across old-old age beyond 80 years. However, in a cohort of individuals aged 40 years and older, Wettstein et al (2022) observed a small increase in AARC-gains and stability in AARC-losses across 5 years. The observed stability in AARC-losses may be due to middle-aged and older adults having the capacity to flexibly adjust their goals (Brandtstädter & Rothermund, 2003).…”
Section: Levels Of Perceived Gains and Losses Across Adulthoodmentioning
confidence: 79%
“…So far, only Wettstein et al (2022) explored whether the change in levels of AARC-gains and AARC-losses differs across the five AARC behavioral domains. This study found that AARC-gains declined in all behavioral domains except for interpersonal relations, where it remained stable.…”
Section: Levels Of Perceived Gains and Losses Across Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the stress vulnerability theory proposed by Lazarus, any social or life event can constitute a potential stressor, but whether the event actually impacts an individual's psychological and physical health depends on the individual's comprehensive assessment of the potential stress and their coping resources [21]. Previous studies also indicate that there are individual differences in the health of the elderly in the face of stress exposure events [22][23][24][25]. However, to date, no study has been able to quantitatively measure the speci c impact of the lifting of restrictions on the health of the elderly and their different groups.…”
Section: Introductionmentioning
confidence: 99%